Análise das propriedades dielétricas e da estabilidade térmica da matriz compósita (fno) - (cto) para uso em antenas ressoadoras dielétricas - Queiroz, Stefany Kariny dos Santos de Souza (2021)
Over the years, the growing development in telecommunications systems has resulted in the need to develop wireless communication technologies using electromagnetic waves. The use of ceramic materials in electrical and electronic systems is becoming more and more constant, as they often provide viable solutions to many of the problems that need to be resolved. Currently, Iron Niobate () has been widely used as a photoanode in converters, gas sensors and electronic devices. Calcium Titanate () has interesting characteristics for technological applications, such as multilayer capacitors, thermistors, dielectric resonators and miniaturization of electronic devices. This work presents the structural and dielectric characterization of composites formed by mixing (FNO) and (CTO), as well as a study on the thermal stability of the new synthesized matrix. The solid state reaction was used to obtain pure FNO and ceramic composites obtained by adding CTO at 20%, 40%, 50% and 80% by weight. X-ray diffraction was used in the structural characterization of these compounds. For the characterization of the dielectric properties, the dielectric permittivity and the loss tangent were measured. A study of the antenna parameters of the samples was also carried out, namely: S11, Smith's Chart and Antenna Gain. Both the dielectric properties and the antenna parameters were obtained through the techniques of Hakki-Coleman, Monopolo and Microstrip Line. Finally, the measurement of the Resonance Frequency Temperature Coefficient (τf) was performed to verify the thermal stability of the material. In the study of this parameter, one looks for materials with the temperature coefficient of the resonance frequency as close to zero as possible, which gives greater thermal stability to the material. It was found that the thermal stability improves with the application of with values ranging from -1293 ppm°C to 850 ppm°C. The 60% concentration of in the sample is the closest to τf equal to zero. In the dielectric characterization, in general, it was observed that the addition of CTO increased the permittivity of the composite matrix and decreased the loss tangent value. The samples working as antennas presented a very satisfactory performance, with a low S11 value and good impedance matching. When compared the measured and simulated results, they showed good agreement and uniformity between them